2016
DOI: 10.1002/jcu.22335
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contrast‐enhanced ultrasonography with virtual touch tissue quantification in the evaluation of focal liver lesions

Abstract: CEUS is superior to VTQ in diagnosing malignant FLLs. Adding VTQ to CEUS did not improve the diagnosis of FLLs. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:347-353, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Twelve studies [1930] used pSWE as the diagnostic imaging modality; the other 3 studies [3133] performed 2D-SWE imaging modality. Ten studies [19, 20, 22, 23, 26, 28, 29, 3133] exclusively reported the cut-off value of the SWV/elasticity in FLL, whereas 4 studies [21, 24, 25, 30] reported the cut-off value of the SWV/elasticity and the cut-off value of the SWV ratio. In addition, 1 study [27] reported the sum of the SWV (FLL and surrounding liver parenchyma).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies [1930] used pSWE as the diagnostic imaging modality; the other 3 studies [3133] performed 2D-SWE imaging modality. Ten studies [19, 20, 22, 23, 26, 28, 29, 3133] exclusively reported the cut-off value of the SWV/elasticity in FLL, whereas 4 studies [21, 24, 25, 30] reported the cut-off value of the SWV/elasticity and the cut-off value of the SWV ratio. In addition, 1 study [27] reported the sum of the SWV (FLL and surrounding liver parenchyma).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that pSWE is a noninvasive and reproducible method that can be used in liver fibrosis assessment, several recent studies sought to investigate pSWE performance for FLL evaluation, with a target to differentiate the large number of FLLs and to characterize their cancerous/benign state [ 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ].…”
Section: Ultrasound Elastography: a New Tool In The Characterizatimentioning
confidence: 99%
“…Table 5 presents a collection of shear wave velocity values (mean in m/s, range) measured by pSWE in different types of FLLs: HCC, metastases, hemangiomas, focal nodular hyperplasia (FNH), and adenomas, as well as the corresponding SWV cut-off values (m/s) for discriminating between the malignant versus benign FLL status. Literature data suggest that malignant FLLs are generally stiffer than their benign counterparts [ 152 , 155 ]; HCCs are overall softer than other malignant tumors [ 140 , 141 , 143 ], with SWS values varying from 2.17 ± 0.85 m/s in the Gallotti study [ 143 ] to 3.07 ± 0.89 m/s in the Guo study [ 146 ]. Several elastographic FLL studies report the following descending order of stiffness, based on the ARFI method: Metastases > HCC > FNH > hemangiomas [ 140 , 147 , 148 ].…”
Section: Ultrasound Elastography: a New Tool In The Characterizatimentioning
confidence: 99%
See 2 more Smart Citations